The Original Definitions of Concepts and Categories of the System of Physical Education in Higher Education of Poland - Andrii Koshura (Pedagogical Discourse, 2015)
In article on the basis of the structurally-system approach the maintenance of basic definitions conceptually and category the device of system of physical training of Poland is considered. To consider different approaches and views of scientists on the content and essence of the definitions, their evolution in the process of development of physical education. The essence of substantially forming definitions of concepts is defined and opened: physical training, values of physical training, the physical training form, criteria of physical training, physical training, physical formation and training, a physical recreation, physical rehabilitation, sports, physical training principles, methods of physical training, means of physical training, the physical training form, physical development, health, physical qualities, physical and motorial readiness. It is established that the semantic content of the categorical apparatus of the system of physical education of Poland is characterized by deep scientific and methodological development and reflects the structural-functional, social, historical, humanistic, pedagogical aspects of the task orientation of the functioning of the system as a whole. The conclusion is drawn that perfection of theoretic-methodological base of system of physical training of Poland descends in the light of euro integration processes as rapprochement of scientific and cultural traditions in uniform educational European space causes necessity of revision of basic bases and the purposes of functioning of system of higher education of Poland as a whole and physical training separately.